(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A rapid sensitive and accurate method for the quantitative and qualitative estimation of bedaquiline was developed using the reverse phase HPLC (RP HPLC) method using acetonitrile and 0.1% trifluoroacetic acid as mobile phase. The system’s suitability was established. The method was validated as per ICH guidelines. The system suitability was established with a good resolution of peak and retention time of 2.27min. The linearity was established at 242nm in the range of 30-180µg/ml, with a correlation corrfiecint of 0.9999. The limit of detection and the limit of quantification was found to be 3µg/ml and 12µg/ml respectively. The accuracy and precision of the process were found to be within the limit of acceptance calculated through relative standard deviation(RSD). The robustness of the process was established with a deliberate change in the injection flow rate, the content of the organic phase and the wavelength. The chromatographic method was found to be specific for the determination of the analyte in a photodegradation study of the knownconcentration of the sample. Hence it can be concluded that the overall process is simple, rapid, accurate and robust enough for the routine analysis of Bedaquiline in pharmaceutical formulation.